CREATIVE WORK : DANCE OF THE AMPHAWA FIREFLIES - ไม้เจริญ ประจักษ์ (Academic Journal Phranakhon Rajabhat University, 2019)
This research aims to study the history and the problems faced by fireflies in Amphawa District, as well as to create a performing art called “ance of the Amphawa Fireflies.” It is a qualitative research. The instruments used in collecting data are: observation form and interview form for focus group. The results are presented in descriptive statistics. According to the results, fireflies in Amphawa district of Samut Songkhram are brackish fireflies. They can be seen from May to October on the bank of the canals, usually on the leaves of cork trees and marshes. When fully grown, these fireflies do not consume any other food except the dew on cork tree leaves. Males and females differ on the glowing abdomen and the antennae. As for the problems, it was found that littering and the throwing of food scraps and waste into the canals make the water become polluted. Consequently, the number of gastropods, food of the larvae, decreases. This has negative effects on the fireflies’cycle of life. Furthermore, the number of cork trees also decreases because motor boats rushing back and forth in the canals make the water spill on the roots of cork trees, making them unable to hold on to the soil surface. Motor boats also reduce the number of firefly larvae along the canals. In addition, global warming directly affects the cycle of life of the fireflies. All of these problems cause the number of Amphawa fireflies in the present time become greatly reduced. The creative work, Dance of the Amphawa Fireflies, include the use of five-instrument Piphat Ensemble, the recital of Thai verses, and the lyrics. The dance gestures are created by imitating the natural movement of the fireflies. There are 10 dance gestures in total. Performers wear beautiful make-up and tie their hair in order to put on the firefly headwear. The costume also reflects the body of firefly. Females and males have different costumes.